DAYA INHIBISI TRIPSIN BEBERAPA EKSTRAK TANAMAN SUKU LEGUMINOSA - Sri Hartati; Hadiman Hadiman (Jurnal Kimia Terapan Indonesia, 1994)
In search of potensial protease inhibitor, especially those which inhibit trypsin activity, preliminary screening of some plant extracts of Legumlnoceae family has been carried out. From 9 (nine) plant extracts examined, those which gave potential enzyme inhibition, were leaf and bark extracts of Caesalpinia pulcherima, and Caliandra chaemotocepala, and bark extract of Delonic regia, Leucaena glauca, and Sesbanla grandlflora . Thin layer chromatographic analysis of the leaf and barkextracts of the plants considered to have the most potensial inhibitor activity indicated that the active principles were of peptide and polyphenollc compounds.